Representatives and directives as core communicative acts: Evidence from illocutionary patterns in Masameer County animation - Ridha, Muhammad Syahid; Nisa', Mauidlotun; Suparno, Darsita; Helmanita, Karlina; Anas, Muhammad (LP2M IAIN Sultan Amai Gorontalo, 2025)
Background: Understanding speech acts in animation is important because misunderstandings can affect communication across cultures. The Masameer County animation, popular among Arabic speakers, contains dialogues with cultural meanings that need deeper study.Aims: This research aims to analyse the categories and functions of illocutionary speech acts in Masameer County's animated dialogue.Methods: This research uses qualitative content analysis with some quantitative support, focusing on pragmatics. The Arabic dialogues and their Indonesian subtitles are transcribed and analysed to identify illocutionary speech acts. John Searle's theory is applied to examine the categories and functions of these speech acts in the Masameer County episodes